The Effectiveness of using stylistics of the group competition and cooperative learning in the development of some motor skills in the art of women in gymnastic - Mouyad, Ghada (Journal of Physical Education, 2014)
Study aimed to identify The Effectiveness of using stylistics of the group competition and cooperative learning in the development of some motor skills in the art of women in gymnastic to identify the methods of learning in the development of some motor skills in the technical in gymnastic, has assumed that the research some statisticallysignificant differences between the tribal and dimensional tests in the development of some motor skills in gymnastic. The study was conducted in the secon d grade class students (Sections health and training) in the physical Education College/ University of Baghdad and has been chosen by the second grad students(training Section) after data collection, analysis and discussion was research the competition is for the collective and cooperative was learning effective in flounce in the development of some motor skills in the art of women in gymnastic & the competition in the collective was more sophisticated and effective methods in the development often variables of night search of collaborative learning style and plenty of style